Pelaksanaan Asas Kebebasan Berkontrak Dalam Perjanjian Waralaba - Syahmina Adani Sabhinaya, Budiharto, Hendro Saptono (Diponegoro Law Journal, 2012)
The rapid growth in Indonesia is also true in the regulation requires the development of contract law. This is because the relationship between the parties' economic actors are constantly evolving both in the provision of goods or services. The development of the legal system prevailing economic co-benefits for economic players in the efficiency of the business in particular to the emergence of multiple enterprise systems that use the uniqueness of the business (brain name) such as business brand, logo, mode of production, marketing and services or which today we know the term franchise. It is a way to boost the economy and provide opportunities for small and medium businesses to try and create equal employment opportunities for the community. This type of research in writing this law using normative research, sources of data in this study is a secondary data source. Data collection methods used in the writing of this law is the study of literature, while the data analysis method used is descriptive qualitative. Franchising is a privilege possessed individuals or business to business system with characteristics certain businesses in order to market their goods or services that have been proven to be used by other parties based on the franchise agreement. Similarly, Article 1 paragraph 1 PP 42 of 2007 describes the notion franchise. Legally, the concept of a new franchise is known in Indonesia in 1997, namely the issuance of Government Regulation (PP) of the Republic of Indonesia Number 16 of 1997 on Franchising. Government Regulation Number 16 of 1997 on franchise has been removed and has been replaced by Government Regulation Number 42 of 2007 on Franchising. then in the making of the agreement or contract must be made in bright and very clear, this is due to reciprocate the trust and have the hope of benefits to both parties will be obtained quickly. Because of that franchise contract is a document that contains a transaction described in detail